Peralihan Hak Atas Tanah dengan Kuitansi Jual Beli - Citra Adityana Setyawan; Antiko Wati (Jurnal Ilmu Kenotariatan, 2022)
Transfer of land rights is more often carried out through buying and selling. In this research, the sale and purchase in question is the sale and purchase of land, with the aim that the buyer can use the land legally. Since the enactment of Law Number 5 of 1960 concerning Basic Agrarian Regulations (UUPA), the sale and purchase of land is further regulated in Government Regulation Number 24 of 1997 concerning Land Registration, which regulates that the sale and purchase of land must be proven by a deed made. on the land before the PPAT. However, buying and selling land without a PPAT deed or an authorized official is still carried out. The objectives to be achieved in this research are as follows: to determine the legal strength of the transfer of land rights with payment receipts in accordance with applicable legal provisions, namely from the perspective of agrarian law. to find out the form of dispute resolution resulting from buying and selling land with receipts. This type of article writing uses normative juridical, with a statutory approach, conceptual approach, and case approach. The results of the research explain that the receipt is categorized as a private deed which does not have binding legal force so that the buyer does not get legal certainty regarding his land. Conclusion Land dispute resolution can be resolved through litigation and non-litigation. Body land can be used in handling/resolving land disputes in accordance with its authority and applicable regulations, namely Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 21 of 2020 concerning Handling and Settlement of Land Cases, Presidential Regulation Number 48 of 2020 concerning the National Land Agency KEYWORDS: Legal Certainly, Transfer of Land Rights, Buying and Selling